Relative cohort size, relative income, and women's labor force participation 1968 - 2010 - Diane J. Macunovich (Institute for the Study of Labor (IZA), 2011)
Relative cohort size - the ratio of young to prime-age adults - and relative income - the income of young adults relative to their material aspirations, as instrumented using the income of older families their parents' age - have experienced dramatic changes over the past 40 years. Relative cohort size has been shown to cause a decline in men's relative wages - the wages of young relative to prime-age workers - due to imperfect substitutability, and the results here show that this applies perhaps even more strongly to women's relative - and absolute - starting wage. Relative cohort size first declined by 30% and then increased by 47%. Results here show that those changes explain about 60% of the declines in women's starting wage - both relative and absolute - in the first period, and 100% of its increase in the second. Relative income is hypothesized to affect a number of demographic choices by young adults, including marriage, fertility and female labor force participation, as young people strive to achieve their desired standard of living. Older family income - the denominator in a relative income variable - increased by 58.6% between 1968 and 2000, and then declined by 9%. Its changes explain 66% of the increase in the labor force participation of women in their first five years out of school between 1968 and 2000, and 75% of its decline thereafter. The study makes use of individual-level measures of labor force participation, with instrumented wages, and employs the lagged income of older families in a woman's year-state-race-education group to instrument parental income and hence material aspirations.
urn:nbn:de:101:1-20110927162
Keywords: J22; 330; relative cohort size; relative income; women's labor force participation; sex ratio; women's hours worked